1991
DOI: 10.1007/bf02051064
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin adhesive in the treatment of perineal fistulas

Abstract: Fifteen patients who developed a persistent perineal sinus after excision of the rectum and eight patients with a perineal fistula appearing after treatment of perineal abscesses were treated with instillation of fibrin adhesive to close the sinus or fistula. In 12 patients, the sinus tracts or fistulas were completely and permanently closed (52 percent). In five patients (22 percent), the fistulas healed after two or three attempts, while, in six patients (26 percent), the method failed to provide lasting clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 9 publications
1
73
0
7
Order By: Relevance
“…Many advantages have been described using fibrin glue in the treatment of anal fistulas. It is simple, repeatable, with minor surgical trauma so sphincter function is preserved and further surgical treatment is not compromised [12,13,14,15,16,17,18,19,20,21,22,23]. Recent publications show promising results using this technique.…”
Section: Introductionmentioning
confidence: 96%
“…Many advantages have been described using fibrin glue in the treatment of anal fistulas. It is simple, repeatable, with minor surgical trauma so sphincter function is preserved and further surgical treatment is not compromised [12,13,14,15,16,17,18,19,20,21,22,23]. Recent publications show promising results using this technique.…”
Section: Introductionmentioning
confidence: 96%
“…Abel et al 12 used cryoprecipitatebased autologous fibrin tissue adhesive (AFTA-C) to treat rectovaginal and complex fistulae in 10 patients and reported an overall success rate of 60%. Hjortrup et al 13 from Denmark reported the use of a commercial fibrin sealant (Beriplast; Behringwerke, Marburg, Germany) in the treatment of 15 patients with persistent perineal sinus after proctectomy and 8 patients with abscess fistulae. They reported an overall closure rate of 74% (17/ 23); however, 5 patients (22%) required 2 or 3 attempts at sealant closure.…”
Section: Commentmentioning
confidence: 99%
“…Fibrin glue was the first biological material used for fistula repair (14), and this has been followed by other noninvasive techniques such as plugging (15), stem cells (16) and Nitinol clips (17). However, only mixed results have been achieved.…”
Section: Discussionmentioning
confidence: 99%